Rapid Genome Evolution and Adaptation of Thlaspi arvense Mediated by Recurrent RNA-Based and Tandem Gene Duplications - Hu, Yanting; Wu, Xiaopei; Jin, Guihua; Peng, Junchu; Leng, Rong; Li, Ling; Gui, Daping; Fan, Chuanzhu; Zhang, Chengjun (Frontiers in Plant Science, 2022)
Retrotransposons are the most abundant group of transposable elements (TEs) in plants, providing an extraordinarily versatile source of genetic variation. Thlaspi arvense, a close relative of the model plant Arabidopsis thaliana with worldwide distribution, thrives from sea level to above 4,000 m elevation in the Qinghai-Tibet Plateau (QTP), China. Its strong adaptability renders it an ideal model system for studying plant adaptation in extreme environments. However, how the retrotransposons affect the T. arvense genome evolution and adaptation is largely unknown. We report a high-quality chromosome-scale genome assembly of T. arvense with a scaffold N50 of 59.10 Mb. Long terminal repeat retrotransposons (LTR-RTs) account for 56.94% of the genome assembly, and the Gypsy superfamily is the most abundant TEs. The amplification of LTR-RTs in the last six million years primarily contributed to the genome size expansion in T. arvense. We identified 351 retrogenes and 303 genes flanked by LTRs, respectively. A comparative analysis showed that orthogroups containing those retrogenes and genes flanked by LTRs have a higher percentage of significantly expanded orthogroups (SEOs), and these SEOs possess more recent tandem duplicated genes. All present results indicate that RNA-based gene duplication (retroduplication) accelerated the subsequent tandem duplication of homologous genes resulting in family expansions, and these expanded gene families were implicated in plant growth, development, and stress responses, which were one of the pivotal factors for T. arvense’s adaptation to the harsh environment in the QTP regions. In conclusion, the high-quality assembly of the T. arvense genome provides insights into the retroduplication mediated mechanism of plant adaptation to extreme environments.